2008
DOI: 10.1007/s00259-008-0806-1
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy response assessment in stage IV melanoma patients—comparison of 18F-FDG-PET/CT, CT, brain MRI, and tumormarker S-100B

Abstract: PURPOSE: This study aims to compare the use of 18F-FDG-PET/CT, CT, brain MRI, and tumormarker S-100B in chemotherapy response assessment of stage IV melanoma patients. METHODS: In 25 patients with stage IV melanoma, FDG-PET/CT and S-100B after 2-3 months (three cycles) of chemotherapy was compared with baseline PET/CT and baseline S-100B. Retrospectively, the response was correlated with the outcome. In patients with clinical suspicion for brain metastases, MRI or CCT was performed. RESULTS: There was agreemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 33 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…In patients with many different cancers including melanoma, the early response to chemotherapy correlates with the significant decrease in [ 18 F]FDG tumor uptake during PET due to an inability of dying or dead cells to actively take up glucose and predicts the overall response to therapy (20). Likewise, in tumor-bearing mice treated with chemotherapy, the decrease in [ 18 F]FDG tumor uptake in comparison with the baseline value was much less pronounced than in mice treated with RIT alone.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with many different cancers including melanoma, the early response to chemotherapy correlates with the significant decrease in [ 18 F]FDG tumor uptake during PET due to an inability of dying or dead cells to actively take up glucose and predicts the overall response to therapy (20). Likewise, in tumor-bearing mice treated with chemotherapy, the decrease in [ 18 F]FDG tumor uptake in comparison with the baseline value was much less pronounced than in mice treated with RIT alone.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significantly longer progression-free survival of PET/CT responders compared with PET/CT nonresponders. As chemotherapy response assessment with serum S-100B tumor marker fails to show correlation with survival, 18F-FDG PET/CT may present a promising tool (Strobel et al 2008). Strobel et al also reached to the same conclusion.…”
Section: Melanomamentioning
confidence: 99%
“…Both 18 F-FDG PET/CT and MRI are sensitive to changes under local and systemic therapy. 18 F-FDG PET/CT has been shown to outperform the tumor marker S100 in the discrimination of responders from nonresponders in a study on stage IV melanoma patients (48). Responders to chemotherapy identified by 18 F-FDG PET/CT in a retrospectively performed evaluation have been proven to have a longer progression-free and overall survival than nonresponders (48).…”
Section: Melanomamentioning
confidence: 99%
“…18 F-FDG PET/CT has been shown to outperform the tumor marker S100 in the discrimination of responders from nonresponders in a study on stage IV melanoma patients (48). Responders to chemotherapy identified by 18 F-FDG PET/CT in a retrospectively performed evaluation have been proven to have a longer progression-free and overall survival than nonresponders (48). Experimental studies performed mainly ex vivo on melanoma xenografts reported that the amount of tumor cell necrosis and the oxygenation status of tumor cells could be assessed using nuclear MR spectroscopy (49).…”
Section: Melanomamentioning
confidence: 99%
See 1 more Smart Citation